2020
DOI: 10.1111/apa.15374
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review found that using thin catheters to deliver surfactant to preterm neonates was associated with reduced bronchopulmonary dysplasia and mechanical ventilation

Abstract: Aim: Surfactant delivery is a cornerstone for managing respiratory distress in preterm neonates, but data on the best surfactant delivery methods have been conflicting. Methods: A systematic literature review using the PubMed, Embase, Cochrane Library and Web of Science databases identified papers published up to November 5, 2019. Additional studies were identified from trial registries, conference proceedings and the reference lists of the selected papers. Results: We identified 15 studies covering 4926 prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
(185 reference statements)
2
23
0
1
Order By: Relevance
“…One possible explanation could be absence of hypoxia and gut ischemia associated with MV or INSURE 30 . Surprisingly, increased focal intestinal perforation with LISA was reported in a study by Hartel et al 26 However, subsequent studies and metanalysis did not report any such side effects 17,31 …”
Section: Short‐term Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…One possible explanation could be absence of hypoxia and gut ischemia associated with MV or INSURE 30 . Surprisingly, increased focal intestinal perforation with LISA was reported in a study by Hartel et al 26 However, subsequent studies and metanalysis did not report any such side effects 17,31 …”
Section: Short‐term Outcomesmentioning
confidence: 97%
“…Terminologies like least invasive surfactant administration (LISA), minimally invasive surfactant technique, and Take Care are used interchangeably for this technique 14–17 . Pandita et al have recently proposed a much needed classification of surfactant administration techniques to make the terminology simple and uniform across the globe.…”
Section: Srt Using Thin Cathetersmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have investigated the impact of minimally invasive surfactant treatment (MIST) or less invasive surfactant administration (LISA), which does not require conventional endotracheal intubation. This approach also reduces BPD, though impacts on developmental outcomes are unknown 42 …”
Section: Influence Of Strategies To Prevent or Treat Bpd On Developmental Outcomesmentioning
confidence: 99%
“…Smaller subsequent studies have also shown improved outcomes [13,14]. A recent systematic review of randomized controlled trials (RCTs) identified that LISA resulted in significantly reduced early intubation rates and BPD compared with INSURE [15]. A recent 2-year follow-up demonstrated that premature infants treated with LISA demonstrated no significant differences in weight, length, or neurodevelopmental outcome compared with infants who received standard treatment [16].…”
Section: Introductionmentioning
confidence: 99%